Analisis Asupan Energi, Karbohidrat, dan Serat dari Pangan Pokok di Wilayah Non Pertanian di Kota Baubau 2022 - Rejeki, Sri; Faradilla, RH Fitri; Elvira, Ilian; Nadila, Nadila (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Intake refers to the food and beverages consumed by an individual within a certain period. It encompasses all nutrients absorbed by the body from food and beverages sources. Adequate and balanced intake is necessary to maintain the health and well-being of the body, including sufficient energy, carbohydrates, protein, fat, vitamins, and minerals. Intake analysis helps evaluate the eating patterns of individuals or populations to support optimal nutritional needs fulfillment. This study aims to analyze the energy, carbohydrate, and fiber intake from staple foods in the non-agricultural area of Baubau City in 2022. The research involved 127 respondents residing in coastal or non-agricultural areas of Baubau City. The data collection method used was the Semi-Quantitative Food Frequency Questionnaire (FFQSQ) through direct interviews. The research findings indicate that the energy, carbohydrate, and fiber intake from staple foods in the non-agricultural area of Baubau City ranged from 20-40%, with carbohydrate intake also ranging from 20-40%, while fiber intake ranged from 0-20%. The most frequent average consumption was 3293.38 kcal/day of rice, 31.77 kcal/day of corn, 67.83 kcal/day of sweet potatoes, and 65.70 kcal/day of cassava. The conclusion of this study is that the energy, carbohydrate, and fiber intake from staple foods in the non-agricultural area of Baubau City are still insufficient. The research recommendation is for the community to pay more attention to daily nutritional intake, especially in terms of energy, carbohydrates, and fiber. The government should enhance nutritional education for the community, especially in non-agricultural areas, about the importance of consuming diverse, balanced, and appropriately portioned foods